(untitled) (Journal of Organizational Psychology, 2020)
A barrier to successful implementation of behavior change strategies may be a chronic staffing crisis leading to poor staffing ratios, competing job tasks, and burnout. The staffing crisis often results in environments in which challenging behaviors receive more interactions. A system oriented approach embedding positive behavior strategies into existing processes helps improve and sustain implementation without magic. This multi-level coaching process demonstrated significant reduction in problem behavior in seven applied settings. Furthermore, participants in the intervention reported increased job satisfaction, including a better relationship with individuals supported and with the supervisors delivering regular onsite feedback.